Effect of fatigue on postural sway in sport-specific positions of young rhythmic gymnasts - Pau, M.; Laconi, I.; Leban, B. (Sport Sciences for Health, 2021)
Background: In rhythmic gymnastics, balance represents a key element in achieving optimal performance. However, there is a lack of data on the modalities with which postural control is impaired by fatigue originated by actual competitive performance. Aims: This study aims to analyze the effect of fatigue consequent to a competitive performance on static balance of rhythmic gymnasts (quantitatively assessed by means of postural sway analysis) for several sport-specific positions. Methods: Fifteen rhythmic gymnasts (mean age 12.7 years) who compete at national and regional levels participated in the study. Their balance was assessed before and after a 90 s performance for 4 unipedal positions (i.e., "ring with hand support", "back split without hand support", "arabesque", and "split with hand support") using a pressure platform. Center-of-pressure (COP) time series acquired for 10 s was processed to calculate sway area, COP path length, and COP displacements in the antero-posterior and medio-lateral directions. Results: After the performance, a generalized increase in postural sway was detected for all the positions tested, with the exception of "arabesque". Sway area doubled for most positions after the performance, while fatigue appears to have a reduced effect on COP displacements in the ML direction, which were found significantly increased only for the "split with hand support" position. Conclusions: The physical effort associated with the performance influences the effectiveness of the postural control system. Coaches could include specific balance exercises even when gymnasts are fatigued to improve their adaptations to competitive conditions and reduce the risk of injuries